Si@SnS2–Reduced Graphene Oxide Composite Anodes for High‐Capacity Lithium‐Ion Batteries. Issue 23 (13th November 2019) - Dai, Jinyan; Liao, Jiang; He, Minyi; Yang, Mengmeng; Wu, Kaipeng; Yao, Weitang
Abstract: One of the key challenges for the development of lithium‐ion batteries is the preparation of high‐performance anode materials. In this paper, a micro/nanostructured Si@SnS2 ‐rGO composite is reported in which Si nanoparticles with a particle size of 30 nm are electrostatically anchored on a 3D reduced graphene oxide (rGO) network and mixed with SnS2 . The step‐wise lithiation/delithiation of SnS2 provided space‐constraining effects to accommodate volume expansion and particle aggregation, thereby alleviating the volume expansion of Si during cycling as well as enhancing the structural stability, whereas the rGO in the 3D network stabilized the composite. The composite had a high specific capacity of 1480.1 mAh g −1 after 200 cycles at a current density of 200 mA g −1 and a high stability at rates of 200–3000 mA g −1 . The capacity attenuation after cycling was only 89.18 %. A stable specific capacity (425.5 mAh g −1 ) was achieved after 600 cycles at a current density of 3000 mA g −1 . Therefore, the micro/nanostructured Si@SnS2 ‐rGO composite is a promising anode material for use in lithium‐ion batteries. Abstract : Inner space limited : A micro/nanostructured Si@SnS2 ‐rGO (reduced graphene oxide) composite was prepared and used as anodes in lithium‐ion batteries. The space‐constraining effects of rGO and layered structure of SnS2 reduced the transmission distance and diffusion barrier of Li + ions and prevented the active particles from accumulating during the electrochemical cycling and alleviated the volume expansion of the material, ensuring excellent electrochemical stability.